2002
DOI: 10.1046/j.1462-2920.2002.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Stratification and seasonal stability of diverse bacterial communities in a Pinus merkusii (pine) forest soil in central Java, Indonesia

Abstract: In Java, Indonesia, many nutrient-poor soils are intensively reforested with Pinus merkusii (pine). Information on nutrient cycles and microorganisms involved in these cycles will benefit the management of these important forests. Here, seasonal effects on the stratification of bacterial community structure in the soil profile of a tropical pine forest are described, and differences in bacterial communities are related to chemical and physical soil parameters. Culture-independent community profiles of litter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Also Shen et al (2008) and Tourna et al (2008) have found temporal shifts in archaeal abundance, and Stres et al (2008) and Tourna et al (2008) evidenced responsiveness of soil archaea to variations in soil temperature and soil moisture. Seasonal changes in soil climate were further closely linked to short-and medium-term variations in resource availability, which further correlated with the quantity and quality of organic matter entering the soil, as it was also previously suggested (Bell et al, 2009;Cookson et al, 2006;Krave et al, 2002). Consequently, total bacterial communities and individual phyla studied were clearly shaped by supply of DOC, DON and mineral N (that is, ammonia, nitrate), which is in agreement with previously published data (Drenovsky et al, 2004;Zak et al, 2003;Alden et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…Also Shen et al (2008) and Tourna et al (2008) have found temporal shifts in archaeal abundance, and Stres et al (2008) and Tourna et al (2008) evidenced responsiveness of soil archaea to variations in soil temperature and soil moisture. Seasonal changes in soil climate were further closely linked to short-and medium-term variations in resource availability, which further correlated with the quantity and quality of organic matter entering the soil, as it was also previously suggested (Bell et al, 2009;Cookson et al, 2006;Krave et al, 2002). Consequently, total bacterial communities and individual phyla studied were clearly shaped by supply of DOC, DON and mineral N (that is, ammonia, nitrate), which is in agreement with previously published data (Drenovsky et al, 2004;Zak et al, 2003;Alden et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…As it appears from unchanged bacterial metabolic diversities in T, S and SF, litter leaching (Qiu et al 2005) and organic matter decomposition (Schmidt et al 2007;Zogg et al 1997) during the plant growth season (summer) were no determinant factors of bacterial activities in our study sites. Similarly, changes in soil moisture content that may have occurred were previously found not to explain the activity of microbial communities Krave et al 2002). Irrespective of the season, differences in plant community composition appeared to explain differences in bacterial metabolic diversity in the present and a previous field study (Rogers and Tate 2001).…”
Section: Seasonal Variationmentioning
confidence: 46%
“…(2000), Krave et al (2002) and Griffiths et al (2003); they were attributed to decrease of either soil moisture or organic C down the soil cores.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Microbial diversity in soil has been analysed by cultureindependent techniques such as PLFA (phospholipid fatty acid) (Fritze et al 2000;Certini et al 2004) or microbial cell DNA (Krave et al 2002;Landeweert et al 2003;Agnelli et al 2004;Hansel et al 2008;Carletti et al 2009). These techniques can overcome problems associated with selective cultivation and isolation of microorganisms from natural samples, by-passing the so called 'great plate count anomaly' (Staley and Konopka 1985;Connon and Giovannoni 2002).…”
Section: Introductionmentioning
confidence: 99%